АСПЕКТЫ ЭКОЛОГИЧЕСКОЙ БЕЗОПАСНОСТИ И ОСНОВЫ ГОСУДАРСТВЕННОЙ ПОЛИТИКИ В ОБЛАСТИ ОХРАНЫ ОКРУЖАЮЩЕЙ СРЕДЫ В КАРАКАЛПАКСТАНЕ - Джумагельдиев, Н.Р. (SCIENCE and SOCIETY, 2021)
The article discusses issues of some aspects of the ecological safety development stages and the basis of state policy in the field of environmental protection in Karakalpakstan. The environmental safety system of the state assumes the presence of certain protective mechanisms of a person from an ecological threat caused by natural and anthropogenic factors leading to an imbalance in the environmental system of the region